(3cJGH GdJQGhjMs - (3GdMfaj GdNQGSGfj, CHh eMeO, GdnqUrOQ GdnqTpgjO, HQgGf GdCFeI, YeQ Hf YHO GdYRjR Hf YeQ Hf eGRI, (B536 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg bGd GdTjN GdEeGe GdCLd GdCSJGP MSGe GdOjf HQgGf GdCFeI GNJda GdeTGjN QMege Gddg aj GdJQGhjM gd jSei SfI bGd HYVge (B: (3dG hgj GdfhGad hbGd HYVge jSei SfI hgh GdUMjM hGfbWY GdNdGa HQhGjI GdMSf Yf CHj MfjaIs
(3BNQgG (B:s
(3bGdhG EPG CNQhgG Edi eG HYO fUa Gddjd de jSJLH hTHggG HJCNjQ GdYTGA hGdUMjM Cfg dG HCS Hg hgh GdeSJMH hGdCaVd dCfgG bjGe Gddjd hbjGe Gddjd aj BNQ Gddjd CaVds
(3efbhdI ef fSNI Gdabjg TjN GdESdGe LeGd GdOjf CHj GdKfGA eMehO Hf CMeO Hf YHO GdSjO GdMUjQjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 51s
(3eYLe GdeDdajf (B2 / 562s
(3cTa GdXfhf (B2 / 1403s
(3GdLhGgQ GdeVjI (B1 / 391s
Keywords: (3Gdabg GdMfHdjs